The Causality Between Entrepreneurial Activities and Regional Economic Growth: Case of Turkey - Semiha Turgut; Aliye Ahu Akgun (European Regional Science Association (ERSA), 2015)
The effect of entrepreneurship on regional economic growth has been a research agenda for the last two decades. Entrepreneurship, by creating employment, fostering competitiveness or affecting employment, somehow contributes to economic development. While entrepreneurship is mostly defined or measured as numbers of self-employed, firm formation, business formation, new firm start-ups, firm births or net entry rates in the empirical studies, regional economic development is defined or measured as, the growth of gross domestic product (GDP), gross value added (GVA) and the change of employment/unemployment rate or productivity. The effect of entrepreneurship on economic growth is mainly seen in two time periods: long term and short term. In the literature, there is evidence on the effect of employment growth in short term and on the effects like crowd-out, displacement, the employment decreases because of the firm closures or employment and productivity growth caused by the new firm formations in long term. The purpose of this article is to find the causality between entrepreneurship and regional economic development in Turkey at the NUTS1 level. In order to reach this aim, entrepreneurship is measured as firm formation and net entry, while regional economic development is measured by GVA, GDP and employment. One of the well-known techniques to identify the causal relations among the variables, correlation is used to measure the length, direction and the weight of the causal affects/relations between regional economic development and entrepreneurship. First, the aim, objectives and detailed framework of this article are given. Then, in the following section, the conceptual and theoretical framework of entrepreneurship and regional economic development is discussed. The case study is given in the third section, with the explanation of data and methodology, a short brief of firm and entrepreneurship policies in Turkey and the effect of entrepreneurship on regional economic development in Turkey at two distinctive periods as 1987-2001 and 2004-2011 separately. This study is the first attempt to show such a relation between entrepreneurship and regional economic growth on the basis of the firm formation. The findings show that the causality between (or effect of) entrepreneurship and regional economic growth changes among regions, which clarifies regional similarities of diversities. Therefore, although the trends of entrepreneurship to affect regional growth in Turkey seem corresponding the findings of the current literature, eastern regions acts differently.
Keywords: L26; O47; 330; entrepreneurship; firm formation; regional economic growth